Mask Detection - et. al., Utkarsh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Covid-19 is causing a severe health crisis in all over the world. India has also been gravely affected by it particularly during current 2nd wave. It’s caused by novel coronavirus. There are some self-precautionary measures suggested to reduce the rate of mitigation of this disease, most important one among them is wearing a face mask. So, in this paper we are putting forward a system that will help authorities curb the spread of coronavirus by detecting the people who are not wearing a mask in a CCTV monitored area when a person not wearing face mask is detected , the system automatically forwards a message to the corresponding authority . The face mask recognition in this paper has been developed using a CNN model with the help of Tensor flow and Open CV. This system has been trained by providing a dataset of images either with or without a mask. Our system has a accuracy of 95.26% in real time .We sincerely hope that our study will be helpful in stopping the spread of coronavirus once implemented.